Effectiveness of Digital Storytelling in Teaching Economics - Jana Nunvarova; Petra Poulova; Pavel Prazak; Blanka Klimova (MDPI AG, 2023)
Digital storytelling is one of the teaching methods that aims to improve motivation of students, critical thinking and learning outcomes. The results of previous research show the successful use of this method in education, but its use in some subjects is still questionable. The aim of the pedagogical experiment, which was conducted in 2021 at six business academies in the Czech Republic, was to discover whether or not digital storytelling contributes to better study results in business subjects taught at high school. A total number of 856 students were randomly divided into two independent groups. In the experimental group, the digital storytelling method was used in the process of teaching. The students in the control group were taught with the standard teaching method-the teacher's explanation with the support of the presentation. By comparing the results from the pre-tests and post-tests of the experimental and control groups, the findings reveal that the students from the experimental group reached higher mean values in the post-test than the students from the control group did.